Mothers experiencing homelessness: implications of stress and coping theory in the development of services - Tischler, Victoria (2007)
Publications and a commentary on them. List of Publications [1] Tischler, V., Cumella, S., Bellerby, T. and Vostanis, P. (2000) A Mental health Service for homeless children and families. Psychiatric Bulletin 24, 339-341 [2] Vostanis, P. Tischler, V., Cumella, S. and Bellerby, T. (2001) Mental health problems and social supports among homeless mothers and children victims of domestic violence. International Journal of Social Psychiatry 47 (4), 30-40 [3] Tischler, V., Vostanis, P., Bellerby, T. and Cumella, S. (2002) Evaluation of a mental health outreach service for homeless families. Archives of Disease in Childhood 86, 158-163 [4] Tischler, V. and Gregory, P. (2002) A resettlement service for homeless and vulnerable parents. Housing, care and support 5 (4), 33-36 [5] Tischler, V., Karim, K., Rastall, S., Gregory, P. and Vostanis, P. (2004) A Family Support Service for homeless children and parents: users'perspectives and characteristics. Health and Social Care in the Community 12 (4), 327-335 [6] Karim, K., Tischler, V., Gregory, P. and Vostanis, P. (2006) Homeless children and parents: short-term mental health outcome. International Journal of Social Psychiatry 52 (5), 447-458 [7] Tischler, V. and Vostanis, P. (2007) Homeless Mothers: Is there a Relationship between Coping Strategies, Mental Health and Goal Achievement? Journal of Community and Applied Social Psychology 17, 85-102 [8] Tischler, V., Rademeyer, A. and Vostanis, P (2007) Mothers experiencing homelessness: mental health, support and social care needs. Health and Social Care in the Community 15 (3), 246-253 [9] Tischler, V. (in press) Resettlement and Reintegration: Mother's Reflections after Homelessness. Community, Work and Family [10] Tischler, V. (under review) I'm not coping, I'm surviving: Understanding coping in vulnerable populations. Qualitative Research in Psychology